HER2 Low Status and Intratumoral Heterogeneity in Epithelial Malignancies and Their Therapeutic Implications - Sharma, Anjali; Kumari, Neetu; Siddh, Snigdha; Nunia, Vandana (Indian Journal of Medical and Paediatric Oncology, 2025)
Human epidermal growth factor receptor 2 (HER2) continues to serve as a critical biomarker in breast cancer, but the introduction of evolving classifications such as HER2-low and HER2-ultra-low presents both opportunities and challenges in precision oncology. Targeted therapies like trastuzumab deruxtecan have broadened treatment possibilities, yet these classifications highlight critical challenges related to standardization, diagnostic precision, and equal access to care. The heterogeneity of HER2 expression adds further complexity, often limiting therapeutic effectiveness. Additionally, the exploration of HER2 as a target in nonbreast cancers underscores the urgent need for rigorous clinical validation in diverse malignancies. To advance HER2-targeted therapies, there is a critical need for comprehensive research, improved diagnostic protocols, and strategies to ensure equitable access to innovative treatments.
Keywords: HER2-low; heterogeneity; treatment strategies; breast cancer; trastuzumab deruxtecan